Mixing Private and Public Service Providers and Specialization - Gersbach, Hans; Halonen-Akatwijuka, Maija (Centre for Market and Public Organisation, University of Bristol., 2005)
We analyze the reform of public sector welfare services such as education. In this paper we compare a mix of private and a public service provider with full privatization. In both cases the suppliers specialize in serving particular customer types. In the mixed institution the government sets the public fee such that service quality does not deteriorate and the price of the private supplier is anchored at comparatively low level. Under full privatization, however, prices escalate to the highest possible level. As a consequence, consumer welfare is higher with a mixed institution – unless the proportion of low-cost customers is high. The mixed institution can also accommodate wealth constraints of customers to some extent.
Keywords: private and public suppliers; specialization; welfare services; mixed institutions